Safety and efficacy of regorafenib in patients with treatment-refractory metastatic colorectal cancer in Turkey: the single-arm, open-label REGARD study - DANE, FAYSAL; YUMUK, PERRAN FULDEN (BMJ PUBLISHING GROUP, 2020)
Objectives Regorafenib improved overall survival in patients with metastatic colorectal cancer (mCRC) refractory to standard therapies in two randomised, phase III trials, but has not been evaluated in Turkey. REGARD evaluated the safety and efficacy of regorafenib in Turkish patients with treatment-refractory mCRC. Design Open-label, single-arm, phase IIIb study conducted between July 2013 and April 2015. Setting 11 tertiary centres in Turkey. Participants Eligible patients were adults with mCRC who had disease progression within 3 months after receiving their last dose of approved standard therapies and who had an Eastern Cooperative Oncology Group performance status <= 1. Patients were excluded if they had previously received regorafenib. Of 139 patients screened, 100 were treated and completed the study, and all 100 were analysed. Fifty-eight per cent were male. Interventions Patients received oral regorafenib, 160 mg once daily, for the first 3 weeks of each 4-week cycle until disease progression, death or unacceptable toxicity. Primary and secondary outcome measures The primary endpoint was safety, assessed by incidence of treatment-emergent adverse events (TEAEs). Progression-free survival (PFS) per investigator was the primary efficacy endpoint. There were no secondary endpoints. Results The median treatment duration was 2.5 months (range 0.1 to 20.6). Ninety-six per cent of patients had at least one TEAE and 77% had a grade >= 3 TEAE. The most common grade >= 3 regorafenib-related TEAEs were hypophosphataemia (11%), fatigue (8%), hyperbilirubinaemia (6%), hand-foot skin reaction (5%), hypertension (5%), anorexia (5%) and increased alanine aminotransferase (5%). TEAEs led to dose reduction in 30% of patients. Regorafenib-related TEAEs led to treatment discontinuation in 17% of patients. Median PFS was 3.1 months (95% CI 2.9 to 3.8). Conclusion The regorafenib safety profile and PFS in REGARD were consistent with the results of previous trials of regorafenib in mCRC. Regorafenib is an option for patients in Turkey with treatment-refractory mCRC.
Keywords: MULTICENTER; TUMORS